Policy Variables and Economic Growth in South Africa: Understanding the Nexus - Ogujiuba, Kanayo; Stiegler, Nancy; Omoju, Oluwasola (Richtmann Publishing, 2012)
The South African economy witnessed profound transformation in the post-apartheid era. This transformation wasattributed to a lot of factors, particularly the various economic and development policies that accompanied the end of apartheidand the political liberation of 1994. This paper investigates the impact of macroeconomic variables on economic growth in SouthAfrica; and identifies policy variables that have been significant in influencing economic growth in the country. The researchadopts a dynamic regression model within the framework of the neo-classical growth model, specifically the adjusted neoclassicalmodel as applied by Ghura & Hadjimichael (1996) and Calanitsis, Basu & Ghura to sub-Sahara Africa. The study foundthat the political liberation of 1994, government investment, maintenance of fiscal discipline and stable exchange rate have apositive impact on economic growth. On the other hand, private investment and terms of trade have negative impact oneconomic growth. The paper recommends that the fiscal and monetary adopted in South Africa should be consolidated, whilethe investment and trade policy should be reviewed to make it growth-inducing.